Assessment of the nutritional quality of fish cultured in Samdihi, an open cast coalpit at the Raniganj Coal Field areas, West Bengal, India. Issue 1 (10th January 2021) - Mandal, Arghya; Biswas, Trisha; Mondal, Niladri Sekhar; Dey, Sukhendu; Patra, Atanu; Das, Subhas; Mondal, Arnab Kumar; Dey, Amit Kumar; Ghosh, Apurba Ratan
Abstract: The present study assessed the nutritional quality of four major teleostean fishes ( Catla catla ; Labeo rohita ; Notopterus notopterus and Oreochromis niloticus ) cultured in the Samdihi, an opencast coalpit (OCP). The physicochemical parameters were within the pisciculture standard limits, and the heavy metal contents of the fish were within safe concentrations and below the target hazard quotient (THQ) level (<1). The zooplankton abundance and density were sufficient as food item for the fish faunas. Ash and moisture contents confirmed the good quality of the fish as food. The results of the other analysed nutritional parameters indicated the total protein content was highest in the herbivorous fish Labeo rohita (85.32 ± 0.61 mg/g), compared to Catla catla, Notopterus notopterus and Oreochromis niloticus (50.34 ± 0.43, 71.32 ± 0.49 and 75.14 ± 0.53 mg/g, respectively). The order of decreasing lipid content was Notopterus notopterus  >  Catla catla  >  Labeo rohita  >  Oreochromis niloticus (7.04 ± 1.02 > 6.01 ± 0.01 > 1.83 ± 0.03 > 1.46 ± 0.04%). The percentage of carbohydrates was highest in the omnivorous Oreochromis niloticus (18.2 ± 0.8), followed by Notopterus notopterus, Catla catla and Labeo rohita (15.1 ± 0.7, 13.9 ± 0.5 and 9.4 ± 0.4, respectively). The sodium content was higher in the column feeders Labeo rohita (82.06 ± 0.61 mg/g) and Notopterus notopterus (81.87 ± 0.61 mg/g) than in the surface feeders Catla catla (69.16 ± 0.55 mg/g) and Oreochromis niloticus (79.33 ± 0.60 mg/g). The potassium content exhibited similar trends, being higher in the column feeders Notopterus notopterus (204.8 ± 1.52 mg/g) and Labeo rohita (199.5 ± 1.81 mg/g) than in the surface feeders Oreochromis niloticus (190.8 ± 1.13 mg/g) and Catla catla (183.2 ± 1.3) mg/g). The trend in iron content was in the order of Oreochromis niloticus  >  Labeo rohita  >  Notopterus notopterus  >  Catla catla (5.60 ± 0.01 > 4.806 ± 0.01 > 4.25 ± 0.01 > 1.303 ± 0.01 mg/g, respectively). The results of the present study highlight the potential and feasibility of conducting pisciculture in the abandoned OCP as a means increasing the economic livelihoods of the core group of people in and around the mining areas of RCF regions. The estimated fish nutritional index (EFNI) analysis also revealed the fish cultured in this OCP exhibited a good nutritional quality standard.